Finding Franklin : the untold story of a 165-year search - Potter, Russell A., 1960- (McGill-Queen's University Press, 2016)
"In 2014 media around the world buzzed with news that an archaeological team from Parks Canada had located and identified the wreck of the HMS Erebus, the flagship of Sir John Franklin's lost expedition to find the Northwest Passage. Finding Franklin outlines the larger story and the cast of detectives from every walk of life that led to the discovery, solving of one of the Arctic's greatest mysteries. In compelling and accessible prose, Russell Potter details his decades of work alongside key figures in the era of modern searches for the expedition and elucidates how shared research and ideas have led to a fuller understanding of the Franklin crew's final months. Illustrated with numerous images and maps from the last two centuries, Finding Franklin recounts the more than fifty modern searches for traces of his ships and crew, and the dedicated, often obsessive, men and women who embarked on them. Potter discusses the crucial role that Inuit oral accounts, often cited but rarely understood, played in all of these searches, and continues to play to this day, and offers historical and cultural context to the contemporary debates over the significance of Franklin's achievement. While examination of the HMS Erebus will undoubtedly reveal further details of this mystery, Finding Franklin assembles the stories behind the myth and illuminates what is ultimately a remarkable decades-long discovery."--